Mechanisms of PKC-dependent Na+ K+ ATPase phosphorylation in the rat kidney with chronic renal failure - Bertuccio, Claudia A. (2009)
The present work was designed to study Na+ K+ ATPase alpha1-subunit phosphorylation in rats with chronic renal failure (CRF) in comparison with normal rats. Na+ K+ ATPase alpha1-subunit phosphorylation degree was measured by binding the McK-1 antibody to dephosphorylated Ser-23 in microdissected medullary thick ascending limb of Henle (mTAL) segments. In addition, the total Na+ K+ ATPase alpha1-subunit expression and activity were also measured in the outer renal medulla homogenates and membranes. CRF rats showed a higher Na+ K+ ATPase activity, as compared with control rats (18.95 +/- 2.4 vs. 11.21 +/- 1.5 micromol Pi/mg prot/h, p < 0.05), accompanied by a higher total Na+ K+ ATPase expression (0.54 +/- 0.04 vs. 0.27 +/- 0.02 normalized arbitrary units (NU), p < 0.05). When McK-1 antibody was used, a higher immunosignal in mTAL of CRF rats was observed, as compared with controls (6.3 +/- 0.35 vs. 4.1 +/- 0.33 NU, p < 0.05). The ratio Na+ K+ ATPase alpha1-subunit phosphorylation/total Na+ K+ ATPase alpha1-subunit expression per microg protein showed a non-significant difference between CRF and control rats in microdissected mTAL segments (2.11 +/- 0.12 vs. 2.26 +/- 0.18 NU, p = NS). The PKC inhibitor RO-318220 10(-6) M increased immunosignal (lower phosphorylation degree) in mTAL of CRF rats to 128.43 +/- 7.08% (p < 0.05) but did not alter McK1 binding in control rats. Both phorbol 12-myristate 13-acetate (PMA) 10(-6) M and dopamine 10(-6) M decreased immunosignal in CRF rats, corresponding to a higher Na+ K+ ATPase alpha1-subunit phosphorylation degree at Ser-23 (55.26 +/- 11.17% and 53.27 +/- 7.12% compared with basal, p < 0.05). In mTAL of CRF rats, the calcineurin inhibitor FK-506 10(-6) M did not modify phosphorylation degree at Ser-23 of Na+ K+ ATPase alpha1-subunit (100.21 +/- 3.00% compared with basal CRF). In control rats, FK 506 10(-6) M decreased the immunosignal, which corresponds to a higher Na+ K+ ATPase alpha1-subunit phosphorylation degree at Ser-23. The data suggest that the regulation of basal Na+ K+ ATPase alpha1-subunit phosphorylation degree at Ser-23 in mTAL segments of CRF rats was primarily dependent on PKC activation rather than calcineurin dependent mechanisms.